Shared and Independent Genetic Basis of Resistance to Bt Toxin Cry2Ab in Two Strains of Pink Bollworm - Fabrick, Jeffrey A. (Sci Rep, 2020)
Evolution of pest resistance threatens the benefits of crops genetically engineered to produce insecticidal proteins from Bacillus thuringiensis (Bt). Field populations of the pink bollworm (Pectinophora gossypiella), a global pest of cotton, have evolved practical resistance to transgenic cotton producing Bt toxin Cry2Ab in India, but not in the United States. Previous results show that recessive mutations disrupting an autosomal ATP-binding cassette gene (PgABCA2) are associated with pink bollworm resistance to Cry2Ab in field-selected populations from India and in one lab-selected strain from the United States (Bt4-R2). Here we discovered that an independently derived, lab-selected Cry2Ab-resistant pink bollworm strain from the United States (BX-R) also harbors mutations that disrupt PgABCA2. Premature stop codons introduced by mis-splicing of PgABCA2 pre-mRNA were prevalent in field-selected larvae from India and in both lab-selected strains. The most common mutation in field-selected larvae from India was also detected in both lab-selected strains. Results from interstrain crosses indicate BX-R has at least one additional mechanism of resistance to Cry2Ab that does not involve PgABCA2 and is not completely recessive or autosomal. We conclude that recessive mutations disrupting PgABCA2 are the primary, but not the only, mechanism of resistance to Cry2Ab in pink bollworm.